1997
DOI: 10.1121/1.419634
|View full text |Cite
|
Sign up to set email alerts
|

Use of pseudo-random sequences and a single microphone to measure surface impedance at oblique incidence

Abstract: The use of a pseudo-random sequence and a single microphone is suggested for the experimental determination of the acoustical properties (surface impedance, reflection coefficient, etc.) of sound-absorbing materials. An experimental system is developed with which the surface impedance and reflection coefficient at oblique incidence are determined from measurements of the impulse-response function sequentially at two locations close to the surface of the material using a pseudo-random sequence and a single micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 16 publications
0
10
1
Order By: Relevance
“…Again this assumes a surface reference plane that is offset 40 mm from the rigid backing. Contrary to the discussion by Li and Hodgson, 33 the results from either microphone separation yielded nearly identical results over the entire frequency range of interest. For the same surface reference plane, the alignment of the fiber also had little effect, although a diminutive resonance was observable over a small frequency range for the parallel alignment tested.…”
Section: B Measurement Of Acoustic Impedance At Oblique Incidencecontrasting
confidence: 75%
See 1 more Smart Citation
“…Again this assumes a surface reference plane that is offset 40 mm from the rigid backing. Contrary to the discussion by Li and Hodgson, 33 the results from either microphone separation yielded nearly identical results over the entire frequency range of interest. For the same surface reference plane, the alignment of the fiber also had little effect, although a diminutive resonance was observable over a small frequency range for the parallel alignment tested.…”
Section: B Measurement Of Acoustic Impedance At Oblique Incidencecontrasting
confidence: 75%
“…This was to minimize errors associated with the assumption of a constant source angle relative to material surface and the microphones. 33 A source separation of 0.4 m was used and incidence angles from 90°͑normal incidence͒ to 40°were tested. For each angle of incidence, impulse response measurements were obtained using maximum length sequences ͑MLS͒ produced by the Brüel & Kjaer DIRAC software.…”
Section: B Measurement Of Acoustic Impedance At Oblique Incidencementioning
confidence: 99%
“…The measurement of the surface impedance in free-field conditions or in situ is at opic of interest since this is an on destructive test and can be performed under realistic mounting conditions. There are manyr eferences in literature addressing the issue of impedance deduction [1,2,3,4] in approaches that calculate the surface impedance from measurements of pressure and /o rp article velocity above asurface. The accuracyofthis deduction is dependent on the description of the sound field above the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Garai [1] has indicated that the reverberation room and tube methods are essentially laboratory methods so they are unsuitable for measuring absorption characteristics in situ. Various reflection methods [11][12][13][14][15][16][17][18][19][20] have been devised and developed to carry out in situ measurement in the expectation that they can solve the problems of other methods. In particular, the methods proposed by Allard et al [11][12][13][14] or Garai [1] constitute efficient and useful reflection methods.…”
Section: Introductionmentioning
confidence: 99%